Development and validation of a liquid chromatographic method to analyze cannabinoids in plants and oils - Arturo-Perdomo, David; Jiménez , Juan Pablo; Hurtado , Andres Mauricio (Revista de Ciencias Agrícolas, 2025)
The therapeutic properties of Cannabis sativa have been widely investigated and have become a subject of great importance for the treatment of diseases such as epilepsy, as well as pain management in patients with cancer, arthritis, and Parkinson’s disease, among others. The commercialization of Cannabis products has flourished due to these properties, highlighting the need to develop analytical methods for quality control of products marketed for medicinal purposes, as well as for Cannabis research. The objective of this work was to develop an HPLC-DAD-based analytical method for Cannabidiol (CBD), Cannabinol (CBN), and Tetrahydrocannabinol, (∆9-THC) cannabinoids tests in commercial Cannabis oils and plant material samples. Regarding the suitability of the system, the developed analytical method exhibited symmetrical peaks, with good resolution and symmetry. The system’s precision was adequate, with relative standard deviation (%RSD) values of less than 5%, and accuracy in terms of recovery greater than 90% for the extractions. Analysis of commercial samples revealed high ∆9-THC content (2.6-42.55 mg/mL) and low CBD content (0-4.3 mg/mL). The plant material sample analyzed correspond to a non-psychoactive chemotype (∆9-THC ≤ 1%) with a higher CBD content (8.0 mg/g). Considering the above, the developed method is suitable for the analysis of plant material and cannabis oils.